Public spending on childcare as an indicator of gender sensitivity of budget - Sikirić, Ana Marija (Mednarodna revija za javno upravo, 2016)
Nowadays, women make more than 60% university graduates, but their status in the labour market does not fully reflect educational achievements, which leads to greater financial dependence of women on men and gender inequality in other areas. To determine the potential solutions to this situation the paper analyses correlation between public spending on childcare services, gender equality in terms of time spent in unpaid work and differences in employment rates of women with children under the age of 6 and women without children in EU. Results confirm significant positive correlation between specified variables and highlight the need to take into account different gender roles of men and women in the decision-making during the budgeting process in order to ensure equal opportunities to male and female labour force in the labour market as a precondition for greater gender equality
Keywords: childcare; enakost spolov; gender equality; javni izdatki; otroški vrtci; otroško varstvo; zaposlovanje; ženske